Simplification or a New Approach to the Construction of the Three Vanishing Points Perspective without Using the Projective Principles - Palamutoğlu, M (WIDE DREAMS PROJECTOS MULTIMEDIA LDA, AV DR ELISIO DE MOURA, 417-1 G, COIMBRA 3030-183, PORTUGAL, 2002)
By applying the projective and descriptive principles, it is exactly possible to draw the three vanishing points perspective of any object like a sky scraper, but this procedure takes so long time and very large area in the picture plane. In order to eliminate this adverse action and to obtain the visible as well as geometrically correct persperctive, it is proceeded this way which we developped. In this work; Firstly, the object has been considered in the form of the rectangle prism which includes its every points and the location of the observer has been chosen on the m-p or MP circle which we exposed in another work [1]. Secondly, it has been taken the picture plane which is perpendicular to the optical axis of the observer. Thirdly, according to this assumption, by using the side and top view of the object it has been fixed the locations of three vanishing points related to the different directions. Fourthly, it has been laterally constructed the perspective of object in the form of straight line in the picture plane. Fifthly, this perspective has been transferred to the frontal position. Finally, this frontal position has been modified by taking the picture plane to the vertical frontal position and observed the simplicity and difference between this perspective and the persective drawn according to the principles of the projective geometry. If desired, this perspective can be magnified through the similarity principles.
Keywords: the m-p circle; visibility requirements; the three vanishing points in perspective; m-p daire; görünürlük gereksinimleri; perspektiften üç kayıp noktalar